Analysis of IGF-1 gene in ayam ketawa (Gallus gallus domesticus) with dangdut and slow type vocal characteristics - ABINAWANTO ABINAWANTO; ALFI SOPHIAN; RETNO LESTARI; ANOM BOWOLAKSONO; PIPIH SUNINGSIH EFENDI; RUDI AFNAN (Society for Indonesian Biodiversity, 2019)
Abstract. Abinawanto, Sophian A, Lestari R, Bowolaksono A, Efendi PS, Afnan R. 2019. Analysis of IGF-1 gene in ayam ketawa (Gallus gallus domesticus) with dangdut and slow type vocal characteristics. Biodiversitas 20: 2004-2010. Insulin-like growth factor 1 (IGF-1) is defined as an essential gene for growth. Therefore, this research aims to identify the polymorphism of the IGF-1 gene from ayam ketawa with the dangdut and slow type vocal characteristics. Twenty male chickens were selected as an animal model. The sample consisted of 10 chickens with the dangdut type and 10 chickens with the slow type. The chickens were all obtained from five areas of the Pinrang district. The RFLP and HRM methods were selected to be used in this research. Results showed that the IGF-1 gene was 622 bp in length, while polymorphism analysis showed that the dangdut and slow type are homozygotic. The unrestricted DNA fragment indicated it after reaction of the restriction enzyme Pst1. Moreover, it confirmed that ayam ketawa with the dangdut or slow type had a similar sequence.